Antioxidant and antiproliferative activities of polysaccharide fractions from litchi pulp. Issue 8 (5th August 2015) - Huang, Fei; Zhang, Ruifen; Dong, Lihong; Guo, Jinxin; Deng, Yuanyuan; Yi, Yang; Zhang, Mingwei
<x xml:space="preserve">Abstract</x> Three litchi polysaccharide fractions (LPFs), LP-4, LP-6 and LP-8, were obtained by fractional precipitation using 40%, 60% and 80% ethanol, respectively.